1993
DOI: 10.1111/j.1524-4725.1993.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Examination of Leg Telangiectases with Duplex Scanning

Abstract: An accurate, functional reconstruction of the subcutaneous venous drainage was accomplished. It was found that telangiectasia was rarely an isolated condition, but was usually associated with incompetence in other elements in the venous drainage of the subcutaneous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Other studies have shown an association between telangiectasia and reflux in adjacent reticular veins. 7,8 Conclusions If anatomy is to be fully understood and therapy appropriately directed in patients presenting with telangiectasia, there is a need for studies employing high definition duplex to track reflux in saphenous systems, reticulars and perforators. GSV (L), great saphenous vein in lower third of the thigh; GSV (U), great saphenous veins just distal to saphenofemoral junction; SSV, the small saphenous vein just distal to the saphenopopliteal junction; CFV, common femoral vein proximal to the saphenofemoral junction; SFV (U), the femoral vein approximately 2 cm distal to the confluence with the profunda femoris vein; FV (L), the femoral vein in the lower third of the thigh; POP (U), the popliteal vein above the skin crease; POP (L), the popliteal vein below the skin crease Values are % (n) with reflux within each grade of telangiectasia N/A, chi-squared test not valid due to low expected counts in some cells …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown an association between telangiectasia and reflux in adjacent reticular veins. 7,8 Conclusions If anatomy is to be fully understood and therapy appropriately directed in patients presenting with telangiectasia, there is a need for studies employing high definition duplex to track reflux in saphenous systems, reticulars and perforators. GSV (L), great saphenous vein in lower third of the thigh; GSV (U), great saphenous veins just distal to saphenofemoral junction; SSV, the small saphenous vein just distal to the saphenopopliteal junction; CFV, common femoral vein proximal to the saphenofemoral junction; SFV (U), the femoral vein approximately 2 cm distal to the confluence with the profunda femoris vein; FV (L), the femoral vein in the lower third of the thigh; POP (U), the popliteal vein above the skin crease; POP (L), the popliteal vein below the skin crease Values are % (n) with reflux within each grade of telangiectasia N/A, chi-squared test not valid due to low expected counts in some cells …”
Section: Discussionmentioning
confidence: 99%
“…In other cases, there is not such a high difference. [3][4][5][6][7][8][9] It is necessary to note that studies searching for perforator vein insufficiency could not find them in every case. These data are not enough to calculate a proportion of cases of shunt and perforator vein insufficiency origin.…”
Section: Discussionmentioning
confidence: 99%
“…The laser-Dopper examination is very sensitive, so minimal technical error or scattering could happen and cause the difference. 3,9,18 In Thibault and colleagues' opinion, the explanation of dilatation in nonreflux cases is a defect in vein wall structure. It seems that perforator vein pathophysiology is supposed to be present in many cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…97 Duplex scanning has also demonstrated telangiectasias to be associated with 'feeding' reticular veins. 98,99 Somjen et al 99 found that 89% of telangiectasias had closely situated incompetent reticular veins. Furthermore, Raymond-Martimbeau and Dupuis 3 found that 71.2% of telangiectasias had direct connections to reticular veins.…”
Section: Cutis Marmorata Telangiectatica Congenitamentioning
confidence: 99%